Aleurone supplementation enhances the metabolic benefits of training in Standardbred mares: impacts on glucose-insulin dynamics and gut microbiome composition - Boshuizen, Berit; De Maré, Lorie; Oosterlinck, Maarten; Van Immerseel, Filip; Eeckhaut, Venessa; De Meeus, Constance; Devisscher, Lindsey; Vidal Moreno de Vega, Carmen; Willems, Maarten; De Oliveira, Jean Eduardo; Hosotani, Guilherme; Gansemans, Yannick; et al. (Frontiers in Physiology, 2025)
IntroductionAleurone, derived from the bran layer of grains like wheat and barley, has demonstrated positive effects on energy metabolism in pigs, mice, and untrained horses, influencing glucose-insulin dynamics and gut microbiome composition. Training itself enhances insulin sensitivity in horses, similar to the improvements in performance capacity observed in human athletes. This study aimed to investigate whether aleurone supplementation provides additional benefits to training by modulating insulin metabolism and gut microbiota in Standardbred mares.MethodsSixteen Standardbred mares (aged 3–5 years) participated in a cross-over study with two 8-week training periods separated by 8 weeks of detraining. Each horse received either 200 g/day aleurone supplementation or a control diet. Insulin metabolism was evaluated using oral (OGTT) and intravenous (FSIGTT) glucose tolerance tests, measuring parameters such as Maximumglucose, AUCglucose, Maximuminsulin, AUCinsulin, Time to peakinsulin (OGTT), Acute Insulin Response to Glucose (AIRg), glucose effectiveness (Sg), and disposition index (DI) (FSIGTT). Fecal samples underwent metagenomic analysis to assess alpha and beta diversity and microbial composition.ResultsTraining alone: Training significantly improved OGTT parameters by decreasing Maximuminsulin (P = 0.005) and AUCinsulin (P = 0.001), while increasing Time to peakinsulin (P = 0.03), indicating enhanced insulin sensitivity. FSIGTT results also showed a decrease in logAIRg (P = 0.044). Training with Aleurone: Aleurone supplementation further reduced FSIGTT AIRg (P = 0.030), logAIRg (P = 0.021) while increasing glucose effectiveness (Sg; P = 0.031). These findings suggest aleurone improves insulin sensitivity, glucose disposal, and fasting glucose regulation beyond training. Microbiome analysis revealed training decreased Pseudomonas, associated with dysbiosis, while aleurone reduced inflammation-associated Desulfovibrio. Beta diversity metrics showed no significant changes.ConclusionAleurone supplementation enhances training-induced improvements in glucose metabolism and fecal microbiota composition, which could offer potential benefits for equine athletes by optimizing metabolic flexibility. It also supports improvements in glucose and insulin dynamics, particularly by further enhancing insulin sensitivity and glucose-mediated disposal. Future studies should investigate the mechanisms of aleurone at the muscle and gut level and explore its potential applications for metabolic disorders such as Equine Metabolic Syndrome.